Kajian Pustaka: Sumber Reactive Oxygen Species (ROS) Vaskular - I Dewa Ayu Susilawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2021)
Increasing amount of vascular reactive oxygen species (ROS) play a key role in the pathogenesis of almost all stages of cardiovascular diseases (CVD), such as atherosclerosis, hypertension, myocardial infartion, etc. This paper aimed to present a brief review of the important vascular sources of ROS. Vascular ROS is mainly produced by enzymatic sources in the vascular cells, i.e. phagocytic inflammatory cells (neutrophils, monocytes/macrophages), and nonphagocytic cells (endothelium, smooth muscle cell and fibroblast). Enzymatic sources of vascular ROS are NADPH oxidase, xanthine oxidase, eNOS, lipoxygenase, cyclooxygenase, and mitochondrial electron transport. In conclusion, over production of ROS induce oxidative burst and will be detrimental for cardiovascular health. A better understanding of ROS would be worwhile for developing method for preventing CVD based on ROS inhibition.